Thigh Ischemia-Reperfusion Model Does Not Accelerate Pulmonary VO2 Kinetics at High Intensity Cycling Exercise - Helal, Lucas; do Nascimento Salvador, Paulo Cesar; de Lucas, Ricardo Dantas; Guglielmo, Luiz Guilherme Antonacci (Frontiers in Physiology, 2019)
Background: We aimed to investigate the effect of a priming ischemia-reperfusion (IR) model on the kinetics of pulmonary oxygen uptake (VO2) and cardiopulmonary parameters after high-intensity exercise. Our primary outcome was the overall VO2 kinetics and secondary outcomes were heart rate (HR) and O2 pulse kinetics. We hypothesized that the IR model would accelerate VO2 and cardiopulmonary kinetics during the exercise. Methods: 10 recreationally active men (25.7 ± 4.7 years; 79.3 ± 10.8 kg; 177 ± 5 cm; 44.5 ± 6.2 mL kg−1 min−1) performed a maximal incremental ramp test and four constant load sessions at the midpoint between ventilatory threshold and VO2 max on separate days: two without IR (CON) and two with IR (IR). The IR model consisted of a thigh bi-lateral occlusion for 15 min at a pressure of 250 mmHg, followed by 3 min off, before high-intensity exercise bouts. Results: There were no significant differences for any VO2 kinetics parameters (VO2 base 1.08 ± 0.08 vs. 1.12 ± 0.06 L min−1; P = 0.30; τ = 50.1 ± 7.0 vs. 47.9 ± 6.4 s; P = 0.47), as well as for HR (MRT180s 67.3 ± 6.0 vs. 71.3 ± 6.1 s; P = 0.54) and O2 pulse kinetics (MRT180s 40.9 ± 3.9 vs. 48.2 ± 5.6 s; P = 0.31) between IR and CON conditions, respectively. Conclusion: We concluded that the priming IR model used in this study had no influence on VO2, HR, and O2 pulse kinetics during high-intensity cycling exercise.